Application of Communication Systems in Biomedical Engineering - Hargas, Libor; Hrianka, Miroslav; Spanik, Pavol (Communications - Scientific letters of the University of Zilina, 2006)
Picture archiving and communication systems (PACS) in biomedical engineering consist of image and data acquisition, storage, and display subsystems integrated by various digital networks. The standard (DICOM 3) is applicable to a networked or an off-line media environment. It allows development and expansion of PACS system. This Standard has been developed with an emphasis on diagnostic medical imaging as practiced in radiology, cardiology and related disciplines. Also the compression methods suitable for image processing are presented in this article. The compression is often realized by reduction of irrelevance or redundancy. There are described lossless and lossy compression methods which can be used for compression of images in biomedical applications and comparison of these methods based on fidelity criteria.